DIABETES SELF MANAGEMENT EDUCATION (DSME) TO IMPROVE DIABETES EDUCATION IN PATIENTS WITH DIABETES MELITUS: LITERATURE REVIEW - Wahyono Wahyono; Fitri Handayani; Niken safitri (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
ABSTRACTBackground: Diabetes mellitus is a chronic disease that requires a change in the healthy behavior of the patient for his recovery. Diabetes Self Management Education (DSME) integrates the four pillars of Diabetes Mellitus Management independently emphasize the behavioral interventions which help people with diabetes to change their lifestyles in terms of diabetic self care.Objective:  Identify diabetes self-management education (DSME) features to improve diabetes education for people with diabetes mellitus. Method: We conducted a literature from 3 online databases like PUBMED, Science Direct and Google Schoolar and used 5 literature for this review.Result and Discussion: The educational process of DSME are assessment, goal setting, education and evaluation based on health promotion model theory. DSME focus on management of DM, nutrition, phisical activity, blood glucose monitoring, avoid/prevent/treat chronic or acute complications, resolve the psichologycal impact and focus on behavioural changes. From 5 studies include in our analysis, we identified that DSME have a good relationship with the positive outcome of DM.Conclusion: DSME is an effective educational method for increasing the good behavioral changes in DM.Keywords: Behaviour, Diabetes Mellitus, Diabetes Self Management Education